1994
DOI: 10.1159/000117005
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Forced Laughter after Unilateral Strokes

Abstract: Forced laughter generally occurs in bilateral or diffuse lesions of the brain and is generally associated with pathologic crying. We report the cases of 3 patients in whom temporary forced laughter occurred after unilateral supratentorial infarction demonstrated by CT scan or MRI. In all cases, the lesion was exclusively subcortical and involved the striatocapsular region. For all patients the laughter occurred during the revovery phase of motor deficit and was ‘pure’ without associated weeping or other clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…Previous literature has shown that lenticulocapsular strokes are frequently related to post-stroke pathological laughter/crying or EI [4,5,9,10,17].We found that as many as a half of the patients with lacune-sized, unilateral lenticulo-capsular strokes had EI on prospective examination. However, it must be pointed out that this figure does not represent the precise incidence of EI after small lenticulocapsular stroke.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Previous literature has shown that lenticulocapsular strokes are frequently related to post-stroke pathological laughter/crying or EI [4,5,9,10,17].We found that as many as a half of the patients with lacune-sized, unilateral lenticulo-capsular strokes had EI on prospective examination. However, it must be pointed out that this figure does not represent the precise incidence of EI after small lenticulocapsular stroke.…”
Section: Discussionmentioning
confidence: 53%
“…For the further analysis of the lesions, the level where the thalamus is well visualized was designated as 'lower (L) level', while one or two cuts higher than this in which corona radiata are seen was designated as 'upper (U) level'. Eight patients (patients 4,6,9,10,12,13,17,24) had lesions only at 'L' level, 8 (patients 2, 3, 5, 7, 18, 20, 21, 25) had lesions only at 'U' level while nine patients (patients 1,8,11,14,15,16,19,22,23) had lesions involving both. In 'L' level, the globus pallidus is well identified by dark signal intensity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 5), recent studies [6,11,12] have revealed that emotional incontinence is not infrequent in patients with unilateral lenticulocapular stroke. Therefore it is likely that the lenticulocapsular lesions of the patients are responsible for the symptoms as well.…”
Section: Discussionmentioning
confidence: 97%
“…PBA is most commonly associated with neural damage (bilateral or unilateral) to the inhibitory prefrontal cortical circuitry descending to diencephalic and brainstem structures that regulate both involuntary and voluntary faciorespiratory mechanisms: the corticohypothalamic and corticobulbar tracts [9,[25][26][27][28][29]. Although PBA has been associated with both bilateral and unilateral lesions, the expression of PBA symptoms may be differentially influenced by laterality [30][31][32][33][34].…”
Section: Pathophysiologymentioning
confidence: 99%